Mempelajari Minat Beli Shampo Khusus Rambut Berhijab: Peran Religiusitas - Muhammad Rizky Ramadhan; Endang Setyawati (Inspirasi Nusantara, 2023)
The phenomenon on need on purchasing the beauty product, particularly shampoos has highlighted this study to go further with wide scopes and spectrums. This study also probes the presence of religiosity on how it shapes the customers’ purchase intention on shampoo which focused on the hijabi women in which establishes a niche field in customers’ segments. The research has conducted a regressive sampling using SmartPLS in proving five dimensions which are ideological, ritualistic, intellectual, consequential, and experiential whether they have significance on the motivation and purchase intention for the Muslimah women in buying the hijabi shampoo. The results presented through the consecutive analysis has derived the magnificent outcome in which there are high rate in consumption and online transaction in singularly purchasing the shampoo products that specialized for the hijabi women. Also, concluding in having a dimension from the religiosity in which has shaped the motive for the Muslimah women to purchase a hijabi shampoo amongst other dimensions.